2004
DOI: 10.1007/s00347-003-0901-4
|View full text |Cite
|
Sign up to set email alerts
|

Vertr�glichkeit eines neuen Kalzium-Alginat-Insertes zur kontrollierten medikament�sen Therapie am Auge

Abstract: This study showed good tolerance of the new calcium-alginate-insert applied to the ocular surface for controlled drug release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This study showed good tolerance of the new calcium-alginate-insert applied to the ocular surface for controlled drug release12. In order to achieve 24 h release profile of water soluble drugs, sodium alginate formulation matrices containing xanthan gum or zinc acetate or both were investigated.…”
Section: Polysaccharides In Pharmaceuticalsmentioning
confidence: 88%
“…This study showed good tolerance of the new calcium-alginate-insert applied to the ocular surface for controlled drug release12. In order to achieve 24 h release profile of water soluble drugs, sodium alginate formulation matrices containing xanthan gum or zinc acetate or both were investigated.…”
Section: Polysaccharides In Pharmaceuticalsmentioning
confidence: 88%